Study on the student body's view of the new teaching methodologies for UniSales engineering courses - Almeida, Miriam Aparecida Ignácio de; Carvalho, Flávio Lúcio Santos de (Brazilian Journal of Production Engineering, 2021)
Currently, a lot is thought and discussed about new teaching methodologies, which are in the different stages of basic education, so that they improve in students: the acquisition of knowledge, interaction and integration of this knowledge with real work situations, where this knowledge is more assertively applied, in addition to the emergence of protagonism, self-confidence, empathy and solidarity and sustainability, also emphasizing all the other skills and competences that the professional market demands. But, while this is all exciting and attractive to the entire academic body, especially the student body, it is very scary and challenging, as it is all new and different from the traditional teaching method that has been used since the beginning of the transmission process. of knowledge. Both for us, the professors, the students, and for the institutions, there are difficulties in adapting the traditional methodology to the new methodologies. Therefore, the purpose of this work is to evaluate the feeling of the student body in face of all the proposed changes to the education system. Questions were made to students, through an online survey with them, checking in detail, expectations, doubts and other information regarding the change to new teaching methodologies. The statistical results showed that students are aware that the changes are relevant due to new market demands, but it is concluded that they are still afraid of how these changes are taking place and if the institutions, the teaching staff and themselves are prepared for such.
Keywords: PBL; Interaction; Academic Knowledge; Practical Experiences; Implementation; Critical Training